Biodiesel Production from Palm Oil Using Micro Tube Reactors: Effects of Catalyst Concentration and Residence Time. (2016) - Azam, Nurul Asyikin Mohd; Uemura, Yoshimitsu; Kusakabe, Katsuki; Bustam, Mohamad Azmi
Abstract: Recognizing the widespread of negative impact from the usage of fossil fuels, biodiesel has been explored to ensure the sustainability of the environment. Recently, microtube reactor has been widely studied for continuous synthesis of biodiesel production. Therefore, this paper is intended to investigate the transesterification of palm oil using micro- and milli-channel reactors. The research was conducted to study the effects of catalyst concentration (0.5-5.0 wt%) and residence time (60-180 s) for two different tube internal diameters of 1.6 and 0.58 mm. The results showed that the oil conversion and FAME yield are greatly influenced by the tube internal diameter, catalyst concentration and residence time. The effect of tube internal diameter may be attributed to mass transfer effect between oil and methanol phases. The microtube reactor achieved more than 95% at 4.5 wt% of catalyst concentration and 180 s of residence time. Besides, the ester content determined by GC-FID analysis is a good estimation to the FAME yield determined by HPLC analysis.